Early childhood education and care reform in Canadian provinces: Understanding the role of experts and evidence in policy change. (23rd March 2016) - A. White, Linda; Prentice, Susan
Abstract: In over half of Canada's provinces, a recent commission has recommended major reform of ECEC systems; in response, provincial governments in nearly all cases have chosen to implement full‐day kindergarten funded by the province and delivered through public schools. We analyze the commission processes that led to changes to investigate the relationship between experts, policy makers, and policy outcomes. Our analysis of processes in BC, Alberta, Ontario, Quebec, and PEI leads us to conclude that governments rarely fully implement the programs supported by the evidence base and recommended by their own experts. Instead, recent policy changes have been driven by a highly selective and path‐dependent approach to the complex issue of early childhood care and education.